Seizures Are Regulated by Ubiquitin-specific Peptidase 9 X-linked (USP9X), a De-Ubiquitinase - Paemka, Lily; Mahajan, Vinit B.; Ehaideb, Salleh N.; Skeie, Jessica M.; Tan, Men Chee; Wu, Shu; Cox, Allison J.; Sowers, Levi P.; Gecz, Jozef; Jolly, Lachlan; Ferguson, Polly J.; Darbro, Benjamin; et al. (PLoS genetics, 2015)
Epilepsy is a common disabling disease with complex, multifactorial genetic and environmental etiology. The small fraction of epilepsies subject to Mendelian inheritance offers key insight into epilepsy disease mechanisms; and pathologies brought on by mutations in a single gene can point the way to generalizable therapeutic strategies. Mutations in the PRICKLE genes can cause seizures in humans, zebrafish, mice, and flies, suggesting the seizure-suppression pathway is evolutionarily conserved. This pathway has never been targeted for novel anti-seizure treatments. Here, the mammalian PRICKLE-interactome was defined, identifying prickle-interacting proteins that localize to synapses and a novel interacting partner, USP9X, a substrate-specific de-ubiquitinase. PRICKLE and USP9X interact through their carboxy-termini; and USP9X de-ubiquitinates PRICKLE, protecting it from proteasomal degradation. In forebrain neurons of mice, USP9X deficiency reduced levels of Prickle2 protein. Genetic analysis suggests the same pathway regulates Prickle-mediated seizures. The seizure phenotype was suppressed in prickle mutant flies by the small-molecule USP9X inhibitor, Degrasyn/WP1130, or by reducing the dose of fat facets a USP9X orthologue. USP9X mutations were identified by resequencing a cohort of patients with epileptic encephalopathy, one patient harbored a de novo missense mutation and another a novel coding mutation. Both USP9X variants were outside the PRICKLE-interacting domain. These findings demonstrate that USP9X inhibition can suppress prickle-mediated seizure activity, and that USP9X variants may predispose to seizures. These studies point to a new target for anti-seizure therapy and illustrate the translational power of studying diseases in species across the evolutionary spectrum.